Distribution and Natural History of the Workerless Inquiline Ant Pogonomyrmex Anergismus Cole (Hymenoptera: Formicidae) - Robert A. Johnson (Psyche: A Journal of Entomology)
Seven colonies of the rare inquiline Pogonomyrmex anergismus Cole were located in New Mexico, two in Hidalgo County, and five in Grant County; P. rugosus was the host for each. Mating flights follow late summer rains. Males mated with colony-mates, mostly inside the nest, and then returned to the nest, Pogonomyrmex anergismus may parasitize host nests over multiple years, with presence of host female alates confirming that the host gyne is not killed. Observations suggest this may be a polygynous species.